Economically Disadvantaged, Incoming Readiness and School Achievement: Implications for Building High-Performing and Effective Schools - James Sunday Etim; Alice Etim; Zachary Blizard (MDPI AG, 2022)
As a result of the 2002 No Child Left Behind Act, North Carolina, like many other states, has created standards and yearly student assessments for K-12 students. Student and school yearly assessments are reported via the North Carolina School Report Cards. Based on the North Carolina School Report Cards, there are several low-performing and failing schools at all levels; schools designated by the State of North Carolina as D or F in the Report Card. This study centered on two research questions: (a) Is there a relationship between incoming readiness and school performance in NC public middle schools? (b) Is there a relationship between economically disadvantaged students and school performance in NC public middle schools? Data was collected from the North Carolina School Report Cards (SRC) datasets (NCDPI, 2019). SRCs are offered for each public school in NC. NC public schools get a report card with their individual school performance score, in addition to other pertinent information, such as teacher and student characteristics. The analysis sample contains two years of data, namely for 2018 and 2017. The dataset includes 850 observations for 425 middle schools. The analysis and results are presented as follows: First, the frequencies of particular performance grades earned by NC middle schools are presented. Second, descriptive statistics are provided and data visuals for the variables associated with the specific research questions a and b, followed by the hypotheses. Third, the hypotheses are tested with the results from the linear regression and ordered logit. Analysis showed evidence of a relationship between incoming student readiness and school performance in NC public middle schools. Larger shares of incoming students considered ready significantly predicts school performance. It is possible to find evidence of a relationship between economically disadvantaged students and school performance in NC public middle schools. Having larger shares of economically disadvantaged students significantly predicts school performance. Based on these findings, a recommendation would be that teachers and schools work to get students ready for middle school in order to improve student performance.